STAKEHOLDERS’ FEEDBACK ON SCHOOL FACILITIES AS A BASIS FOR TECHNOLOGY-BASED ENHANCEMENT - Pepito, Joseph C (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
This study assessed the stakeholders’ feedback on the school facilities of Consolacion Central School in Cebu, Philippines, during the school year 2017-2018 as a basis for enhancing the existing facilities by integrating the technology-based enhancement. The study utilized the descriptive survey method using frequency counts, simple percentages, and ranking to process the data provided by the one hundred respondents composed of parents, learners, and community leaders of the barangay where the school is located. Four were identified of the ten identified areas: site, buildings, classrooms, and administrative offices. Based on the findings, it was concluded that the educational facilities of Consolacion Central School need to be improved by utilizing the new technology to ensure the safety and conduciveness of the learning environment and to meet the high demands of quality basic education as a foundation of learning to every child in the locality and the country as a whole. The attainment of excellent educational facilities requires an improvement plan which is why it is proposed and adopted.